Dual-process reasoning in charitable giving: Learning from non-results - Zachary Grossman; Joël J. van der Weele (Games, 2017)
To identify dual-process reasoning in giving, we exposed experimental participants making a charitable donation to vivid images of the charity's beneficiaries in order to stimulate affect. We hypothesized that the effect of an affective manipulation on giving would be larger when we simultaneously put the subjects under cognitive load using a numerical recall task. Independent treatment checks reveal opposite responses in men and women and cast some doubt on the reliability of our mainstream treatment manipulations and assessment tools. We find no evidence for dual-process decision-making, even among women, whose responses to the manipulations conformed most to our expectations. These results highlight the need for caution in the use of these common manipulations, the importance of independent manipulation checks, and the limitations of dual-process models for understanding altruistic behavior.
Keywords: C91; D64; 330; cognitive load; dual-process; charitable giving; dictator games; experimental economics